2000
DOI: 10.1002/(sici)1097-4652(200003)182:3<339::aid-jcp4>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and anticancer therapy-induced modifications on metabolism mediated by carnitine system

Abstract: An efficient regulation of fuel metabolism in response to internal and environmental stimuli is a vital task that requires an intact carnitine system. The carnitine system, comprehensive of carnitine, its derivatives, and proteins involved in its transformation and transport, is indispensable for glucose and lipid metabolism in cells. Two major functions have been identified for the carnitine system: (1) to facilitate entry of long-chain fatty acids into mitochondria for their utilization in energy-generating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 0 publications
0
30
0
2
Order By: Relevance
“…Anorexia is often another symptom of cachexia. The Walker 256 carcinosarcoma rat model, adopted in the present investigation, is the most studied experimental model of cancer cachexia (Peluso et al 2000) and induces most of the syndrome-correlated symptoms (Kurth et al He et al 2003;Piffar et al 2003), which are present in cancer patients (Heymsfield and McManus 1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anorexia is often another symptom of cachexia. The Walker 256 carcinosarcoma rat model, adopted in the present investigation, is the most studied experimental model of cancer cachexia (Peluso et al 2000) and induces most of the syndrome-correlated symptoms (Kurth et al He et al 2003;Piffar et al 2003), which are present in cancer patients (Heymsfield and McManus 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Our aim was to assess whether there was correspondence with such changes and leptin synthesis by the retroperitoneal, mesenteric and epididymal WAT in Walker 256 tumour-bearing rats, a solid tumour model which induces cachexia and has been widely used in studies concerning this condition (Peluso et al 2000). During the study, we found that the adipose tissue of the tumourbearing rats was invaded by infiltrating cells.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, when palmitoylcarnitine in the presence of carnitine is provided to HT-29 cells, an increased generation of O 2 -. inside mitochondria is observed that promotes apoptosis initiation [4]. Carnitine here was proven to be a limiting factor for fatty acid import into mitochondria in colon cancer cells [1,5] with no apoptosis observed when only palmitoylcarnitine was provided to the cells [4]. In the present study, we investigated whether fl avone, beside increasing mitochondrial pyruvate or lactate transport, can increase fatty acid import into 3 101 mitochondria as a fuel for mitochondrial beta-oxidation and respiration.…”
mentioning
confidence: 95%
“…In our study we observed no influence of L-carnitine on anthracycline action-e.g., on survival times, relapse rate and major clinical parameters. This confirms previous studies indicating that carnitine treatment reverses the dysfunction of FA metabolism in nontumorous tissues of cancer patients without affecting anti-cancer therapeutic efficacy (Cruciani et al 2004;Peluso et al 2000;Sayed-Ahmed et al 2000).…”
Section: Discussionmentioning
confidence: 99%